Iridescence from tuned microstructures in poly(octamethylene terephthalate) - Yu-Zhe Huang; Selvaraj Nagarajan; Widyantari Rahmayanti; Li-Ting Lee; Eamor M. Woo (eXPRESS Polymer Letters, 2023)
Poly(octamethylene terephthalate) (POT), self-assembled with periodically banded aggregates, are analyzed using polarized-light optical microscopy and scanning electron microscopy. POT can display banded spherulites (with blue/orange tint colors), depending on crystallization temperature. 3D interior morphology dissection is conducted to reveal the gratinglike architecture of POT periodically banded crystal aggregates. The grating assembly is composed of onion-like layers (i.e., corrugate-board cross-hatches), with distinctly discontinuous interfaces existing between the successive layers, and each layer is composed of tangential-oriented fibrous lamellae and plate-like radial-oriented ones. Novel findings confirm that the interior gratings of ring-banded POT are comparable to the grating micro-structures commonly seen in nature’s biospecies such as butterfly’s wings. The POT microstructures could be finely modulated and tailored-made to functional applications as interfacial coating materials for performing photonics iridescence.